Dalit Literature: A Contemporary Perspective - Buwa, Mr. Vilas Rupnath (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: As a major literary trend in India through Indian regional languages and translations. Dalit literature is marked for self-assertion of Dalits, subalterns, lower strata of Indian caste-class-religion-language-capital ridden society through poetry, plays, short stories, self-narratives, and oral performances challenging inhuman treatment, atrocities, inequality, and the so-called mainstream literary and critical conventions. Dalit literature is emerged as an outcome of the exploitative nature of Indian caste system.The ideology is drawn from Buddha, Charvak, Kabir, JyotiraoPhule, Karl Marx and Dr. B. R. Ambedkar. At this stage, Dalit literature needs to be stabilized at theoretical and critical level, considering western critical approaches in order to explore the essence of Dalit literature on the contemporary literary and critical canvass. This paper attempts to focus onthe term ‘Dalit’, the elements of Dalit literature, Dalit literature in English, the term ‘Dalit identity’ and how it reflected in Dalit literature, theorizing Dalit literature and literary critical standards, précising Dalit literature in the recent literary trends in India, comparison and contrast of Dalit literature with the Anglo-American and third world literary tradition, the issues raised by Dalit literature and their validity in the present era, the sources and forces of Dalit literature and future course of Dalit literature.